ASUHAN KEPERAWATAN PADA Tn.M SKIZOFRENIA HALUSINASI PENDENGARAN DENGAN INTERVENSI MENGONTROL HALUSINASI BERCAKAP-CAKAP DENGAN ORANG LAIN DI RUMAH SAKIT DR. RM SOEDJARWADI KLATEN - Fikri Wiliyanto; Fida Dyah Puspasari; Sudiarto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
In Indonesia, the prevalence of schizophrenia/psychosis is around 6.7 per 1000 households. Hallucinations are a condition that befalls individuals with mental disorders which results in changes in the patient's subjective perception, which is characterized by the patient experiencing sensations such as sound, sight, taste and touch without any clear stimulation. If not treated immediately, the symptoms will get worse and can cause harm. self. One effective method for controlling schizophrenia is to encourage people to interact or converse with other people. The benefit of the activity is that it prevents hallucinations from occurring. The aim of the research is to determine the description of nursing care for patients with schizophrenic auditory hallucinations with a focus on the act of conversing with other people. Using descriptive methods by managing patients arranged in nursing care, functions to create systematic, real and precise descriptions of the facts.  The results of focused therapeutic actions on conversing with other people for 3 days can reduce the signs and symptoms of auditory hallucinations. This is proven when conversing with other people, the patient focuses on the conversation and can avoid whispers that are not real to the patient. It was concluded that the technique of conversing with other people can prevent signs and symptoms of auditory hallucinations.